PERAN STRATEGIS DAERAH ATAMBUA (RI) – BOBONALO (TIMOR LESTE) DALAM TATA KELOLA PERTAHANAN DAN KEAMANAN NASIONAL BERDASARKAN UNDANG-UNDANG NOMOR 3 TAHUN 2002 TENTANG PERTAHANAN NEGARA - Yuwono Prianto; Hery Firmansyah (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2017)
The paradigm of boundary management of Indonesia Timor Leste region in Atambua Bobonalo has the implementation to the boundary region condition which is relatively isolated and left behind from the economic aspect, defense aspect and national security aspect as well as the legal aspect. It is also required the welfare approach besides the security approach and also the boundary management system which is well and professionally organized. The boundary region needs more attention from the govemment for that side defense and security is very dependent. Infrastructure in Timor Leste boundary development shall be adequate in the context of defense and security such as the weapon system supply, infrastructure and suprastructure boundary development, recognition/protection of indigenous people rights regulations, the drafting and stipulating the cross-boundary regulations as well as the rule of law supremacy and the improvement of the professionalism of govemment officials. All in all, we need to maintain the nationalism to the society at the boundary region, and the implementation of policy pattern approach which would not leave the local wisdom behind.